Clarice Lispector e a potencialidade melancólica: um estudo psicanalítico - Bonadio, Andrea Cristina (2013)
This dissertation aims to conduct a study of the melancholic potential, through a psychoanalytic reading of the biography of Clarice Lispector. My intention in using the biography of Clarice Lispector is due to the fact that the writer presents characteristics that can be understood as melancholic potential. Thus, it is possible to assume, that Clarice Lispector is melancholic potential herself, due perhaps to a possible libidinal and identificatory history, where there was a premature loss of maternal love, and this caused narcissistic disqualification in its primordial psychic constitution. For this research, delivery of freudian theory and some authors followers of Freud, who contributed to a better understanding of the study of melancholy, as Lucia Maria Violante, Laplanche and Pontalis, among others